Emerging roles for Interleukin-11 in disease. (4th March 2019) - Nguyen, Paul M.; Abdirahman, Suad M.; Putoczki, Tracy L.
Abstract: Interleukin (IL)-11 belongs to the IL-6 family of cytokines, discovered over 30 years ago. While early studies focused on the ability of IL-11 to stimulate megakaryocytopoiesis, the importance of this cytokine to inflammatory disease and cancers is only just beginning to be uncovered. This review outlines recent advances in our understanding of IL-11 biology, and highlights the development of novel therapeutics with the potential for clinical targeting of signaling by this cytokine in multiple diseases.